(untitled) (Research, Society and Development, 2025)
Alcohol abuse is a relevant problem in the health field, affecting physicians and medical students, with impacts on clinical practice and patient safety. This study aims to analyze the prevalence of alcohol abuse among these professionals, identify associated factors and discuss its consequences. This is an integrative literature review, with a survey of articles in databases such as SciELO, LILACS and MEDLINE, published between 2000 and 2024. The results show that physicians and medical students have high rates of alcohol consumption, often related to occupational stress, exhausting work hours and easy access to psychoactive substances. In addition, there is a higher prevalence among men and professionals in specialties such as anesthesiology and surgery. Alcohol abuse compromises the quality of care, increases the risk of medical errors and affects the mental health of professionals. It is concluded that preventive measures and institutional support are essential to mitigate these impacts, ensuring patient safety and the health of doctors and students.